Technological characteristics of the white fibre of Huacaya alpaca in the Andean region of Apurimac - Vásquez O., Rutnis (2015)
The study aimed to estimate five technological characteristics of the white fibre of Huacaya alpaca of a rural community of the Andean region of Apurimac, Peru. Fibre samples (n=405) were taken from the middle of the rib area prior to shearing. The variables studied were: mean diameter of fibre (MDF), coefficient of variation of fibre diameter (CVDF), comfort index (IC), curvature index (ICur) and spinning fineness (FiHi), by sex and age group according to teeth (DL=Deciduous teeth; 2D=2 permanent teeth; 4D=4 teeth; BLL=all teeth). The MDF for males and females was 19.6 and 20.1 µm respectively (p<0.05), where values increased with age (p<0.05). No statistical difference was found by sex or age for CVDF. The IC was 96.8% in males and 95.5% in females (p<0.05), decreasing with age (p<0.05). The ICur was similar between sexes and difference due to age was only observed between DL with 4D and BLL (p<0.05). The FiHi was different between sexes (p<0.05) and between Dl and BLL (p<0.05). Significant and positive relationships was found between MDF with FiHi and IC with ICur, and negatives between MDF with IC, MDF with ICur, IC with FiHi, ICur with FiHi, and ICur with CVDF. These results indicate that in this area of the country there are alpacas with good potential in fibre quality.